Towards replacing diesel fuel in low explosive production with eco-friendly materials: An application of fuzzy group decision making methods - Abiodun I. Lawal; Olayemi Y. Ogundipe; Musa A. Idris; Aminat F. Ajeboriogbon; Kazeem B. Adedeji; Babatunde K. Adeoye (Next Research, 2026)

Provenance, tectonic settings, depositional conditions, and diagenetic features of the late Cretaceous (Coniacian–Santonian) Fika Shale, Upper Benue Trough, Northeastern Nigeria: Implications for hydrocarbon potential - Abdulwahab Bello; Musa B. Usman; Shehu Mukkafa; Ibrahim A. Kwami; Usman Abubakar; Abduljamiu O. Amao; Anas M. Salisu; Khalid Al-Ramadan; Muhammad A. Ismail; Abubakar S. Maigari; Ahmed I. Haruna; Bandar D. Al-Otaibi; et al. (Journal of African Earth Sciences, 2026)

Carcinogenic risk assessment, hydrogeochemical signatures, and irrigation suitability of groundwater within Ajaokuta and environs, North Central, Nigeria - K. O. Musa; F. A. Akpah; O. C. Akakuru; G. O. Aigbadon; A. C. Nanfa; M. M. Shaibu; J. B. Jimoh (International Journal of Energy and Water Resources, 2026)

Development and validation of SR-DISVAXFIC: A mobile phone application for estimating the herd-level financial impact of small ruminant diseases and the potential benefits of vaccination in the field - Megan E. Rawlins; Adeyinka J. Adedeji; Victoria I. Ifende; Sandra I. Ijoma; Rebecca B. Atai; Joel Y. Atuman; Gambo Panzam; Haruna W. Gotom; Idris H. Adamu; Anas U. Musa; Isa M. Sani; Paul Adamu; et al. (Preventive Veterinary Medicine, 2026)

Bangko plant (Rhizophora mucronata) as a nature-based solution for coastal toxic metal pollution - M. Al Mustawa; P. Taba; B. Musa; R. Mardiyanti (International Journal of Environmental Science and Technology, 2026)

Identifying the Worthy and Compatible Excipients Through In-Silico Approach for Rational Formulation Development: Insights into the Acyclovir and Trimethoprim Formulations - Abhijeet H. Patil; Meera C. Singh; Mohammed Sakib Musa; Minhaz Abdullah Al Mueid; Hossain Mohammed Reza; Md. Eshak Enan; Mahadie Hasan Jahad; Jamil Azhar Shakil; Shibam Mondal; Rajesh B. Patil (Journal of Pharmaceutical Innovation, 2025)

Innovative resource recovery: converting discarded disposable diapers (D3) into activated carbon using Box–Behnken design - D. R. S. I. Shah; N. F. Anuar; S. Z. Roslan; M. Musa; W. M. A. W. Daud; A. B. Alias; N. Aghamohammadi (International Journal of Environmental Science and Technology, 2025)
This study aims to optimize the production of activated carbon from discarded disposable diapers (D3AC) using Box–Behnken design (BBD) under response surface methodology. Biochar (D3B) was initially produced via carbonization at 900 °C for 90 min under nitrogen flow, followed by physical activation with CO 2 . The BBD model demonstrated strong reliability (R 2 = 0.9972), effectively predicting the influence of activation temperature, holding time, and CO₂ flowrate on surface area development. Under optimized conditions, D3AC exhibited a BET surface area of 1235.32 m 2 /g, significantly higher than that of D3B (479.79 m 2 /g), with a well-developed microporous structure. In contrast, D3B displayed higher total pore volume and ash content. These findings confirm the successful enhancement of porosity and surface characteristics through parameter optimization and support the feasibility of thermochemical conversion using statistical design. Graphical abstract

Biomarker signatures in host rocks and their co-occurring fossil plants from northern Scotland - Olumuyiwa T. Akinsanpe; Adebola O. Akinsanpe; Solomon A. Adekola; Oluwaseye P. Oyetade; Waheed G. Akande; Musa B. Usman; Abdulwahab M. Bello; Uzochukwu K. Benjamin; Adeniyi O. Olusanya; Chikezie Emele (Organic Geochemistry, 2025)

Linking provenance and diagenesis to reservoir quality evolution of sandstones: The Paleocene-Eocene Kerri-Kerri Formation, northeastern Nigeria - Abdulwahab M. Bello; Musa B. Usman; Abduljamiu O. Amao; Anas M. Salisu; Khalid Al-Ramadan; Usman Abubakar; Shehu Mukkafa; Ibrahim A. Kwami; Lukman U. Chiroma; Murtada Al-Hashem; Abubakar Yusuf; Abubakar S. Maigari; et al. (Marine and Petroleum Geology, 2025)

Diagenesis and reservoir quality evolution of estuarine sandstones: Insights from the Cenomanian-Turonian Yolde Formation, northern Benue Trough, NE Nigeria - Abdulwahab M. Bello; Musa B. Usman; Abduljamiu O. Amao; Khalid Al-Ramadan; Murtada Al-Hashem; Aliyuda Kachalla; Usman Abubakar; Anas M. Salisu; Shehu Mukkafa; Ibrahim A. Kwami; Oluwafemi E. Aro; Muhammad Naveed Butt; et al. (Marine and Petroleum Geology, 2024)

Ethnobotany of Food Plants Used in the Kimvula Territory (Kongo Central Province) in Congo, DR [Ethnobotany of Foods Plants in Congo, DR] - Lemmy K. Lassa; Guy B. Ilumbe; Jean-Paul Koto-Te-Nyiwa Ngbolua; Apollinaire M. Biloso; Da Musa Y. Masens; Jean-Pierre M. Habari; Félicien L. Lukoki (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2024)

Elucidating the structural basis for the enhanced antifungal activity of amide derivative against Candida albicans: a comprehensive computational investigation - Eban L. Kechi; Chioma B. Ubah; Musa Runde; Aniekan E. Owen; Obinna C. Godfrey; Daniel C. Agurokpon; Michael O. Odey; Uwem O. Edet; Bassey O. Ekpong; Solomon O. Iyam; Innocent Benjamin; Gopinath Sampathkumar (In Silico Pharmacology, 2024)

A global assessment of environmental and climate influences on wetland macroinvertebrate community structure and function - Luis B. Epele; Emilio A. Williams‐Subiza; Matthew S. Bird; Aurelie Boissezon; Dani Boix; Eliane Demierre; Conor G. Fair; Patricia E. García; Stephanie Gascón; Marta G. Grech; Hamish S. Greig; Michael Jeffries; et al. (Global Change Biology, 2024)
Estimating organisms' responses to environmental variables and taxon associations across broad spatial scales is vital for predicting their responses to climate change. Macroinvertebrates play a major role in wetland processes, but studies simultaneously exploring both community structure and community trait responses to environmental gradients are still lacking. We compiled a global dataset (six continents) from 756 depressional wetlands, including the occurrence of 96 macroinvertebrate families, their phylogenetic tree, and 19 biological traits. Using Bayesian hierarchical joint species distribution models (JSDMs), we estimated macroinvertebrate associations and compared the influences of local and climatic predictors on both individual macroinvertebrate families and their traits. While macroinvertebrate families were mainly related to broad‐scale factors (maximum temperature and precipitation seasonality), macroinvertebrate traits were strongly related to local wetland hydroperiod. Interestingly, macroinvertebrate families and traits both showed positive and negative associations to the same environmental variables. As expected, many macroinvertebrate family occurrences were positively associated with temperature, but a few showed the opposite pattern and were found in cooler or montane regions. We also found that wetland macroinvertebrate communities would likely be affected by changing climates through alterations in traits related to precipitation seasonality, temperature seasonality, and wetland area. Temperature increases may negatively affect collector and shredder functional groups. A decrease in precipitation could lead to reductions in wetland area benefiting drought‐tolerant macroinvertebrates, but it may negatively affect macroinvertebrates lacking those adaptations. Wetland processes may be compromised through broad‐scale environmental changes altering macroinvertebrate family distributions and local hydroperiod shifts altering organism traits. Our complementary family‐based and trait‐based approaches elucidate the complex effects that climate change may produce on wetland ecosystems.

Drought conditioning of rhizosphere microbiome influences maize water use traits - Kelsey R. Carter; Abigael C. Nachtsheim; L. Turin Dickman; Eric R. Moore; Sangeeta Negi; John P. Heneghan; Anthony J. Sabella; Christina R. Steadman; Michaeline B. N. Albright; Christine M. Anderson-Cook; Louise H. Comas; Rose J. Harris; et al. (Plant and Soil, 2023)
Background and Aims Beneficial plant–microbe interactions can improve plant performance under drought; however, we know less about how drought-induced shifts in microbial communities affect plant traits. Methods We cultivated Zea mays in fritted clay with soil microbiomes originating from contrasting environments (agriculture or forest) under two irrigation treatments (well-watered or water limited). Using this design, we investigated whether water conditioning was carried forward through the microbiome to affect a subsequent plant cohort that was subjected to either a well-watered or water limited treatment. Results Regardless of the microbiome-origin, plants inoculated with a microbiome from a water limited legacy had traits that allowed them to avoid stress but conserve water. They produced longer roots to explore soil, generated greater soil dissolved organic carbon, potentially stimulating the microbiome, and slower soil water content loss during drought. A well-watered legacy resulted in plants that delayed permanent stomatal closure and higher photosynthetic nitrogen use efficiency. In plants with a forest-originated microbiome, a well-watered legacy and water treatment also resulted in higher rates of photosynthesis and stomatal conductance. Conclusion These results demonstrate that soil microbiomes can be developed to influence plant drought performance, impacting crop resilience, using short-term microbial conditioning.

Linking diagenesis and reservoir quality to depositional facies in marginal to shallow marine sequence: An example from the Campano-Maastrichtian Gombe Sandstone, Northern Benue Trough, NE Nigeria - Abdulwahab M. Bello; Musa B. Usman; Muhammad A. Ismail; Shehu Mukkafa; Usman Abubakar; Ibrahim A. Kwami; Khalid Al-Ramadan; Abduljamiu O. Amao; Murtada Al-Hashem; Anas M. Salisu; Aliyuda Kachalla; Muhammad B. Abubakar; et al. (Marine and Petroleum Geology, 2023)

Investigation of groundwater repositories in Modakeke-Ife, southwestern, Precambrian Basement Complex, Nigeria - Augustine B. Arogundade; Charles I. Adenika; Musa O. Awoyemi; O. Afolabi; Adams A. Bakare; Olaide S. Hammed (Sustainable Water Resources Management, 2023)

Bonding, bridging and linking social capital combinations for food access; A gendered case study exploring temporal differences in southern Malawi - Ailish Craig; Craig Hutton; Frank B. Musa; Justin Sheffield (Journal of Rural Studies, 2023)

Linking household access to food and social capital typologies in Phalombe District, Malawi - Ailish Craig; Craig Hutton; Laura A. Lewis; Frank B. Musa; Justin Sheffield (Sustainability Science, 2023)
Food security remains a major sustainability challenge in many parts of Sub-Saharan Africa. Food security has numerous determinants that are complex and interlinked, with one of them being social capital. Social capital reflects an individual’s, household’s, or community’s social networks, social interactions, and social support systems that can be mobilized in times of need to maintain, among others, livelihoods or food security. This study aims to further understand how typologies of social capital are associated with household food security in Southern Malawi, with a focus on access to food. We unpack social capital into three typologies, namely bonding, bridging, and linking social capital, and establish which one is most strongly associated with household access to food, and whether this varies by the gender of the household head. To achieve this, we analyze secondary data from 382 households collected through the Malawian Fourth Integrated Household Survey (IHS4), using principal axis factor analysis and logistic regression analysis. Our findings demonstrate that bonding and bridging social capital are associated with better household access to food, while linking social capital was associated with lower household access to food. Bonding social capital was most strongly associated for female-headed households and linking social capital for male-headed households, highlighting that there are differences between such households. This work confirms observations from other related studies in Sub-Saharan Africa exploring the interface of social capital and food security. It also highlights the importance of both acknowledging the gender of the household head and of unpacking social capital into its typologies when considering food security.

Impact of improved hermetic storage on food insecurity and poverty of smallholder cowpea farmers in Northwestern Nigeria - Abraham A. Adomi; Tahirou Abdoulaye; Ahmed B. Mohammed; Zilkifli Abdu; Shehu A. Musa; Dieudonne՛ Baributsa (Journal of Stored Products Research, 2023)

Designating the First Vernal Pool Micro-Reserve in a Buffer Zone of Wadi Qana Protected Area, Palestine - Mazin B. Qumsiyeh; Elias N. Handal; Banan Al-Sheikh; Mohammad H. Najajreh; Issa Musa Albaradeiya (Wetlands, 2022)

Minimally Invasive Intracerebral Hemorrhage Evacuation: A review - Mishek J. Musa; Austin B. Carpenter; Christopher Kellner; Dimitri Sigounas; Isuru Godage; Saikat Sengupta; Chima Oluigbo; Kevin Cleary; Yue Chen (Annals of Biomedical Engineering, 2022)

First isolation and molecular characterization of pseudorabies virus detected in Turkey - Gizem Aytogu; Eda B. Toker; Ozkan Yavas; Berfin Kadiroglu; Ozer Ates; Musa Ozgur Ozyigit; Kadir Yesilbag (Molecular Biology Reports, 2022)

Pest activity and natural enemy diversity in stored dry date (Phoenix dactylifera L. (Arecales: Arecaceae)) in the Northern Guinea Savannah Agroecological Zone - D. M. Mailafiya; L. J. Bamaiyi; B. T. Magaji; I. P. Musa; A. J. Kwanashie; O. O. Banwo; L. Y. Bawa (International Journal of Tropical Insect Science, 2022)

Effect of hemoglobin polymorphism on performance traits in indigenous chicken genotypes in Nigeria - M. Orunmuyi; H. Muhammad; A. A. Musa; A. K. Olutunmogun; B. I. Nwagu (Tropical Animal Health and Production, 2020)

A molecular prevalence survey on Anaplasma infection among domestic ruminants in Khartoum State, Sudan - Nagwa M. Eisawi; Abdel Rahim M. El Hussein; Dina A. Hassan; Azza B. Musa; Mohammed O. Hussien; Khalid A. Enan; Mohammed A. Bakheit (Tropical Animal Health and Production, 2020)

Geochemical characteristics and origin of the Neoproterozoic high-K calc-alkaline granitoids in the northern part of Mandara hills, northeastern Nigeria - Musa B. Girei; Tavershima Najime; Paul O. Ogunleye (Acta Geochimica, 2020)

Healthcare Economics of Hydrocephalus After Aneurysmal Subarachnoid Hemorrhage in the United States - Syed M. Adil; Beiyu Liu; Lefko T. Charalambous; Musa Kiyani; Robert Gramer; Christa B. Swisher; Laura Zitella Verbick; Aaron McCabe; Beth A. Parente; Promila Pagadala; Shivanand P. Lad (Translational Stroke Research, 2019)

The effects of repetitive stress on tat protein-induced pro-inflammatory cytokine release and steroid receptor expression in the hippocampus of rats - Khayelihle B. Makhathini; Oualid Abboussi; Musa V. Mabandla; William M. U. Daniels (Metabolic Brain Disease, 2018)

Current knowledge of metabolomic approach in infectious fish disease studies - C‐F Low; M Z H Rozaini; N Musa; B Syarul Nataqain (Journal of Fish Diseases, 2017)
The approaches of transcriptomic and proteomic have been widely used to study host–pathogen interactions in fish diseases, and this is comparable to the recently emerging application of metabolomic in elucidating disease‐resistant mechanisms in fish that gives new insight into potential therapeutic strategies to improve fish health. Metabolomic is defined as the large‐scale study of all metabolites within an organism and represents the frontline in the ‘omics’ approaches, providing direct information on the metabolic responses and perturbations in metabolic pathways. In this review, the current research in infectious fish diseases using metabolomic approach will be summarized. The metabolomic approach in economically important fish infected with viruses, bacteria and nematodes will also be discussed. The potential of the metabolomic approach for management of these infectious diseases as well as the challenges and the limitations of metabolomic in fish disease studies will be explored. Current review highlights the impacts of metabolomic studies in infectious fish diseases, which proposed the potential of new therapeutic strategies to enhance disease resistance in fish.

New aristolochic acid and other chemical constituents of Aristolochia maurorum growing wild in Jordan - Mohammed B. Al-Barham; Hala I. Al-Jaber; Mahmoud A. Al-Qudah; Musa H. Abu Zarga (Natural Product Research, 2017)

Cleaner tanning process for the manufacture of upper leathers - A. E. Musa; B. Madhan; Swarna V. Kanth; J. Raghava Rao; B. Chandrasekaran; G. A. Gasmelseed (Clean Technologies and Environmental Policy, 2010)

Determination of Exposure to Polycyclic Aromatic Hydrocarbons in Some Work Groups in Turkey by Measurement of 1-Hydroxypyrene Levels in Urine - İ. Ateş; M. Yılmazer-Musa; B. Yücesoy; A. Karakaya (Bulletin of Environmental Contamination and Toxicology, 2004)